Result of study on developing forest seed region in Mongolia - S, Jamyansuren; B, Udval; N, Batkhuu; J, Bat-Erdene; Fischer, Michael (Proceedings of the Mongolian Academy of Sciences, 2019)
In foreign countries, motor roads and railroads are usually used as borders of forest seed regions. In the case of Mongolia, this method is not suitable in view of the sparse population, large distribution area of forests and the huge territory of the country. Therefore, this study used topographical features to determine the borders of the seed regions. Satellite images in combination with Digital Elevation Model (DEM) make it possible to define rivers, streams and mountain ridges as the borders of forest seed regions. Overall, we identified 19 seed regions for Siberian larch and 12 regions for Scots pine, 9 regions for Siberian pine, 6 regions for Siberian fir and 9 seed regions for Siberian spruce forests. Due to a lack of genetic-selection studies in Mongolia, these proposed forest seed regions can be considered as a preliminary effort with an opportunity to be updated and improved based on more detailed research results. The forest seed regions and maps will play important role as fundamental material for establishing a permanent forest seed supply based on genetic-selection characteristics of the forests in different regions in Mongolia.